2014
DOI: 10.1175/jcli-d-12-00273.1
|View full text |Cite
|
Sign up to set email alerts
|

North Atlantic SSTs as a Link between the Wintertime NAO and the Following Spring Climate

Abstract: In this paper a potential seasonally lagged impact of the wintertime North Atlantic Oscillation (NAO) on the subsequent spring climate over the European region is explored. Supported by the observational indication of the wintertime NAO-spring climate connection, a modeling approach is used that employs the International Centre for Theoretical Physics (ICTP) atmospheric general circulation model (AGCM) as a stand-alone model and that is also coupled with a mixed layer ocean in the North Atlantic. Both observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 58 publications
3
18
0
Order By: Relevance
“…Actually, the positive TriNA in May was following the strong positive NAO in winter of 2017/2018 ( Figure 5b). As documented by some previous studies, the winter NAO could produce the spring triple SSTA mode in the North Atlantic, which induced the downstream wave train over the Eurasian continent (Herceg-Bulić & Kucharski, 2014;Hu et al, 2011;Wu et al, 2009;Wu & Wu, 2019;Zuo et al, 2012). A similar behavior has also been reported in boreal autumn (Wang et al, 2018).…”
Section: Linkage To Sst Anomaly In the North Atlanticsupporting
confidence: 78%
“…Actually, the positive TriNA in May was following the strong positive NAO in winter of 2017/2018 ( Figure 5b). As documented by some previous studies, the winter NAO could produce the spring triple SSTA mode in the North Atlantic, which induced the downstream wave train over the Eurasian continent (Herceg-Bulić & Kucharski, 2014;Hu et al, 2011;Wu et al, 2009;Wu & Wu, 2019;Zuo et al, 2012). A similar behavior has also been reported in boreal autumn (Wang et al, 2018).…”
Section: Linkage To Sst Anomaly In the North Atlanticsupporting
confidence: 78%
“…With respect to the SST anomaly, more research may be carried out on any temporal lead between this anomaly and the response in spring precipitation over southern China. For example, Herceg‐Bulić and Kucharski () observed that the wintertime North Atlantic Oscillation has an impact on the spring climate over Europe through the North Atlantic SST, which might also influence the spring rainfall over southern China due to the EU pattern. We will undertake a similar analysis of the precursory signals for southern China in future research.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…A discussion on the suitability of the model to reproduce realistic transient eddy feedbacks can be found in Abid et al (2015). Examples of the North Atlantic storm tracks response to surface forcings in the model can be found in Kucharski and Molteni (2003) and in Herceg-Bulić and Kucharski (2014).…”
Section: Methodsmentioning
confidence: 99%